2010
DOI: 10.1128/aem.01027-10
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Flurbiprofen by Cunninghamella Species

Abstract: The biotransformation of the fluorinated anti-inflammatory drug flurbiprofen was investigated in Cunninghamella spp. Mono-and dihydroxylated metabolites were detected using gas chromatography-mass spectrometry and fluorine-19 nuclear magnetic resonance spectroscopy, and the major metabolite 4-hydroxyflurbiprofen was isolated by preparative high-pressure liquid chromatography (HPLC). Cunninghamella elegans DSM 1908 and C. blakesleeana DSM 1906 also produced a phase II (conjugated) metabolite, which was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…elegans DSM 1908 is very well known to be a model for mammalian drug metabolism (Asha and Vidyavathi 2009), and we have shown previously that the suspended mycelia transform the drug flurbiprofen to mono-and di-hydroxylated metabolites (Amadio et al 2010). This drug was used to study the capability of the biofilm for biotransformation.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…elegans DSM 1908 is very well known to be a model for mammalian drug metabolism (Asha and Vidyavathi 2009), and we have shown previously that the suspended mycelia transform the drug flurbiprofen to mono-and di-hydroxylated metabolites (Amadio et al 2010). This drug was used to study the capability of the biofilm for biotransformation.…”
Section: Resultsmentioning
confidence: 90%
“…In contrast, the fungus Cunninghamella elegans has been shown to transform a broad range of drugs and xenobiotics to the same metabolites as humans (Asha and Vidyavathi 2009;Amadio et al 2010;Amadio and Murphy 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, they and their metabolites are detected in the aquatic environment (Chowdhury et al 2003;Amadio et al 2010;Hata et al 2010).…”
Section: Mefenamic Acid Indomethacin and Flurbiprofen Biodegradationmentioning
confidence: 99%
“…In the environment, fungi which able to transform this drug are nevertheless found. Amadio et al (2010) revealed flurbiprofen transformation to 4 0 -hydroxyflurbiprofen and 3 0 -hydroxy-4 0 -methoxyflurbiprofen, as well as to 3 0 ,4 0 -dihydroxyflurbiprofen by Cunninghamella species: C. elegans DSM 1908, C. echinulata DSM 1905 and C. blakesleeana DSM 1906. C. elegans strains DSM 8217 and DSM 63299 were able to transform flurbiprofen only to 4 0 -hydroxyflurbiprofen and 3 0 -hydroxy-4 0 -methoxyflurbiprofen.…”
Section: Mefenamic Acid Indomethacin and Flurbiprofen Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation